Розвиток рефлексії майбутніх фахівців соціономічного профілю в процесі професійно-особистісної підготовки - Марусинець Мар’яна; Maryana Marusynets (Видавництво «Код», 2025)
Резюме. У статті порушено питання підготовки майбутніх фахівців соціономічного профілю в умовах сучасних викликів. Окреслено сутність, особливості, специфіку, вказано на місце і роль рефлексії в процесі оволодіння провідною – навчальною діяльністю у професійноособистісному становленні фахівців. Особливий акцент зроблено на розкритті внутрішнього потенціалу здобувачів освіти в процесі оволодіння ними навчальною діяльністю – розкритті себе у собі (саморефлексія), осмисленні і переосмисленні свого досвіду, отриманих знань із викликаними, зумовленими життєво складними ситуаціями суб’єктів взаємодії (рефлексія).

Abstract. The article raises the issue of training future specialists with a socio-economic profile in the context of modern challenges. It outlines the essence, features and specifics of reflection and indicates its place and role in the process of mastering the leading educational activity in the professional and personal development of specialists. Particular emphasis is placed on the provision on revealing the inner potential of students in the learning process – revealing oneself within oneself (self-reflection), comprehending and rethinking one's experience, the knowledge gained from the vitally complex situations caused by the subjects of interaction (reflection). The step-by-step development of reflection in mastering a future profession is revealed. These are abilities, interests, desires, the reflection of which leads to self-determination of a profession and awareness of the motives for learning and, through their analysis, the formation of professional and personal goals. An example of reflection on learning motives can be the analysis of probable self-realisation in the anticipated activity and the choice of a professional path (applied, research, managerial, socially oriented, etc.), which is the most desirable and at the same time realised thanks to the acquisition of a set of subject-specific and basic professional competences, the provision of assistance aimed at supporting individuals in difficult, critical moments of life, crises and problematic situations. Reflection of future specialists in this sense is manifested in the intensity of meaningful experiences, the breadth of psychological time, and the desire to show empathy towards another person. It is emphasised that reflection is considered a characteristic of a developing personality. It develops in the activity in which it manifests itself – learning, in a specially organised educational environment. Afterwards, it continues to form in professional activity. The role of reflective processes in ensuring the subjective position of a future specialist is determined by two mechanisms: self-change and self-determination. The mechanism of self-change is reflection and self-reflection, and in professional and personal development, it is professional reflection. Education based on constant reflective activity of students will contribute to the formation of professional and personal qualities necessary for professional development, opportunities to meet modern standards and requirements of the market and employers.
Development of reflection in future specialists with a socio-economic profile in the process of professional and personal training
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: підготовка майбутніх фахівців соціономічного профілю; рефлексія; саморефлексія; навчальна діяльність; здобувачі освіти; рефлексна позиція